Physico‐chemical and toxicological assessment of liquid wastes from olive processing‐related industries - Pierantozzi, Pierluigi (2012)
BACKGROUND: In the last few years, agricultural uses of waste waters from olive processing-related industries have been gaining interest mainly with a view to composting or bio-fertilizers. The present work examines physico-chemical, toxicological and geno-toxicological properties of three liquid wastes, namely olive mill wastewater (OMWW), olive wet husk and olive brine. The effect of OMWW spreading on soil microbial activity and biomass was also evaluated. RESULTS: Data from Artemia salina and Lactuca sativa toxicity tests indicated high levels of lethality, and inhibitory effects on seed germination and seedling growth of all olive wastes. The genotoxicity assays using Allium cepa tests showed contrasting results. At high concentrations, olive wastes caused inhibition or suppression of mitosis. However, they did not produce induced anaphase aberrations. Data on reversion of Salmonella thyphimurium strains using the Ames test indicated that the olive wastes did not present mutagenic activity. Results from the field experiment showed that OMWW at a 500 m3 ha−1 had the highest values of both soil microbial activity and biomass after 3 months of the amendment application. CONCLUSION: This work adds new data for environmental risk assessment of olive industrial wastes. Direct use of olive wastes for agricultural purposes should be limited owing to their possible chemotoxic, phytotoxic and antimicrobial effects.